Pengaruh strukture aktiva, profitabilitas, pertumbuhan penjualan, dan size perusahaan terhadap struktur modal pada perusahaan makanan dan minuman yang terdaftar di BEI periode 2014-2018 - Sembiring, Indiani; Sitinjak, Susi L.; Herdina Hutabarat, Debi; Aisyah Nasution, Siti (Jurnal Paradigma Ekonomika, 2021)
This study aims to determine and test the effect of assets structure, profitability, sales growth, and firm size on capital structure partially and simultaneously of food and beverage companies. Determination of the sample used in this study was purposive sampling technique which amounted to 11 companies with a year observation of five years and data obtained from the financial statements of food and beverage companies at www.idx.co.id. The data analysis method used is multiple linear regression analysis.Based on the results obtained that assets structure has a significant effect on capital structure. Meanwhile, profitability, sales growth, and firm size didnâ€™t have a significant effect on capital structure. Simultaneous hypothesis test results obtained that the assets structure, profitability, sales growth, and firm size have a significant effect on capital structure.Â  Â